8.20. Wykonaj działania: \rho(x) = 0, 75x ^ 7 + 5/8 * x ^ 6 + 0, 125x ^ 5 + 2 P P(x) = – 4x ^ 3 – 12x ^ 2 + 0, 5x + 0, 4; P(x) = 5x ^ 6 – 2sqrt(2) * x ^ 5 + 4x – 1; P(x) = x ^ 4 – x ^ 3 + sqrt(3) * x ^ 2 – sqrt(2) a) (2x ^ 6 – 3x ^ 4 + 2x) – (x ^ 4 + 8x ^ 2 + 4x – 1) + x ^ 6 + 5x ^ 4 + 6x ^ 2 b) (- 3x ^ 4 + 5x ^ 3 – 6) – (4x ^ 4 + 2x ^ 3 + 4x) – (- 7x ^ 4 + 3x ^ 3 + 8) c) 7x ^ 7 – 6x ^ 5 + 2x – (4x ^ 5 + 3x ^ 2 – 6) – (7x ^ 7 – 10x ^ 5) d) 12x ^ 3 – (x ^ 7 + 4x ^ 3) – (14x ^ 3 – 5x ^ 7) .

8.20. Wykonaj działania: \rho(x) = 0, 75x ^ 7 + 5/8 * x ^ 6 + 0, 125x ^ 5 + 2 P P(x) = – 4x ^ 3 – 12x ^ 2 + 0, 5x + 0, 4; P(x) = 5x ^ 6 – 2sqrt(2) * x ^ 5 + 4x – 1; P(x) = x ^ 4 – x ^ 3 + sqrt(3) * x ^ 2 – sqrt(2) a) (2x ^ 6 – 3x ^ 4 + 2x) – (x ^ 4 + 8x ^ 2 + 4x – 1) + x ^ 6 + 5x ^ 4 + 6x ^ 2 b) (- 3x ^ 4 + 5x ^ 3 – 6) – (4x ^ 4 + 2x ^ 3 + 4x) – (- 7x ^ 4 + 3x ^ 3 + 8) c) 7x ^ 7 – 6x ^ 5 + 2x – (4x ^ 5 + 3x ^ 2 – 6) – (7x ^ 7 – 10x ^ 5) d) 12x ^ 3 – (x ^ 7 + 4x ^ 3) – (14x ^ 3 – 5x ^ 7) .